BOOK REVIEW: William A. Bleiziffer, ‟Disciplina sacramentelor şi cultul divin.Consideraţii canonice referitoare la sacramentul botezului”, Presa Universitară Clujeană, Cluj Napoca, 2016, 242 p. - COSTE-DEAK, Traian-Radu (Studia Universitatis Babeș-Bolyai Theologia Catholica, 2017)
With great joy we salute the appearance of the first analyses and considerations in the field of the Oriental Canon Law, in the academic and cultural space of the Romanian Greek-Catholic Church, after its emergence from the shadows of the catacombs. No illusion should be created as referred to this aspect, it is obvious that a great number of articles and papers have been written and published in the spectrum of the Oriental Canon Law in different periodicals and series of academical works; however the publishing of a book which starts a systematic canonic analysis of some clear and fundamental topics, from the canonic point of view, for the life of the Church and as a support of pastoral activity, is materialized through the publication of this book: Disciplina sacramentelor şi cultul divin. Consideraţii canonice referitoare la sacramentul botezului.